Android Based Application for Public Complaints at Yuliddin Away Regional Hospital - Sukma Achriadi Sukma; Fardiansyah; Asmaidi; Sera Delta Tanjung (LPPM Politeknik Aceh Selatan, 2021)
The Yuliddin Away Regional General Hospital as an institution that conducts individual health services in a complete manner often experiences obstacles in providing maximum services to the community. So that in some cases, received complaints from the public. So far, these complaints are accommodated with complaint boxes in each service division, but this method is difficult to get accurate information and relatively takes a long time. The use of information and communication technology in the form of applications is expected to improve responsive and informative service quality. Through the Android-based Complaints application, it is easy for the public to provide advice and criticism of the services of Yuliddin Away Hospital. Implementation procedures include observation, problem identification, literature study, design, system development, and application. The communication mechanism between the user and the system uses an interface. The application interface for public complaints at Yuliddin Away Regional Hospital includes Admin Flowchart Design, User Flowchart Design, Use Case Design, and Database Design. The application is very helpful for hospital staff in managing community complaints as suggestions in weekly and monthly meetings in order to improve the quality of Yuliddin Away hospital services.